Differential remodelling of mitochondrial subpopulations and mitochondrial dysfunction are a feature of early stage diabetes - Mamas (Scientific Reports, 2022)
Abstract Mitochondrial dysfunction is a feature of type I and type II diabetes, but there is a lack of consistency between reports and links to disease development. We aimed to investigate if mitochondrial structure–function remodelling occurs in the early stages of diabetes by employing a mouse model (GENA348) of Maturity Onset Diabetes in the Young, exhibiting hyperglycemia, but not hyperinsulinemia, with mild left ventricular dysfunction. Employing 3-D electron microscopy (SBF-SEM) we determined that compared to wild-type, WT, the GENA348 subsarcolemma mitochondria (SSM) are? ?2-fold larger, consistent with up-regulation of fusion proteins Mfn1, Mfn2 and Opa1. Further, in comparison, GENA348 mitochondria are more irregular in shape, have more tubular projections with SSM projections being longer and wider. Mitochondrial density is also increased in the GENA348 myocardium consistent with up-regulation of PGC1-a and stalled mitophagy (down-regulation of PINK1, Parkin and Miro1). GENA348 mitochondria have more irregular cristae arrangements but cristae dimensions and density are similar to WT. GENA348 Complex activity (I, II, IV, V) activity is decreased but the OCR is increased, potentially linked to a shift towards fatty acid oxidation due to impaired glycolysis. These novel data reveal that dysregulated mitochondrial morphology, dynamics and function develop in the early stages of diabetes.
This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.
Keywords: R Medicine; RC Internal medicine